The issue of aligning language self-assessment with the final Russian language exam results of foreign students in the preparatory department - Soloveva, Anna Andreevna; Saikina, Ol'ga Sergeevna (Филология: научные исследования, 2024)
The article addresses the issue of developing linguistic self-esteem among students in the preparatory department at the Russian State Agrarian University—Moscow State Agricultural Academy named after K. A. Timiryazev. THe servey took place in 2022-2023 the studying Russian for 7-9 months and reached the approximate language level A2-B1. Through a survey conducted among students with varying levels of self-esteem (high, average, and low level), the study identifies distinct patterns in the formation of linguistic self-esteem before and after examinations. It defines the significance of language self-esteem within the context of various concepts and terminology related to an individual's self-image. The research reveals how self-esteem fluctuates based on students' awareness of their results on the Russian language exam. The methodology employed to obtain these results involved a questionnaire assessing how students gauge their language proficiency both prior to and following the examination. It was discovered that proficiency in the Russian language correlates with the level of self-esteem. Notably, in groups studying Russian as a foreign language, there are instances of students exhibiting low self-esteem yet achieving high results, as well as those with high self-esteem but low performance, alongside students demonstrating average results and an accurate self-assessment. Consequently, the study highlights a disconnect between the actual level of knowledge and the students' perceptions of their capabilities. In both cases, the disparity between the actual situation and self-assessment is regarded as an issue. However, when comparing underestimated and exaggerated self-assessments, it appears that the latter case has a more detrimental impact on the outcome.